Children’s Voices at Midnight: Can the Subaltern Speak in Rushdie’s Narrativisation of History? - Galván Álvarez, Enrique (Estudios Ingleses de la Universidad Complutense, 2009)
This essay deals with Salman Rushdie’s night’s Childrenm the perspective of “narrativised history”, discussing and problematising one of the most common interpretations of this novel as “magical realism”, as a way of voicing the Subaltern. From a methodological point of view this is an attempt to elaborate a reflection upon the textual limits of historiography and the potentialities of “magical realist” narratives as instruments for the voicing of what Foucault called “subjected knowledges”.